2017
DOI: 10.2352/issn.2470-1173.2017.7.mwsf-328
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles of Convolutional Neural Networks for Multimedia Forensics

Abstract: Convolutional neural networks (CNNs) have received significant attention due to their ability to adaptively learn classification features directly from data. While CNNs have helped cause dramatic advances in fields such as object and speech recognition, multimedia forensics is fundamentally different problem compared to other deep learning applications. Little work exists to guide the design of CNN architectures for forensic tasks. Furthermore, it is still unclear which forensic tasks can be performed using CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 26 publications
0
99
0
Order By: Relevance
“…Furthermore, it has been shown that deep features from a CNN trained for camera model identification transfer very well to other forensic tasks such manipulation detection [23], suggesting that deep features related to digital forensics are general to a variety of forensics tasks. 1) Architecture: To build a forensic feature extractor, we adapt the MISLnet CNN architecture developed in [7], which has been utilized in a number of works that target different digital image forensics tasks including manipulation detection [6], [7], [30] and camera model identification [23], [30]. Briefly, this CNN consists of 5 convolutional blocks, labeled 'conv1' through 'conv5' in Fig.…”
Section: A Learning Phase a -Feature Extractormentioning
confidence: 99%
“…Furthermore, it has been shown that deep features from a CNN trained for camera model identification transfer very well to other forensic tasks such manipulation detection [23], suggesting that deep features related to digital forensics are general to a variety of forensics tasks. 1) Architecture: To build a forensic feature extractor, we adapt the MISLnet CNN architecture developed in [7], which has been utilized in a number of works that target different digital image forensics tasks including manipulation detection [6], [7], [30] and camera model identification [23], [30]. Briefly, this CNN consists of 5 convolutional blocks, labeled 'conv1' through 'conv5' in Fig.…”
Section: A Learning Phase a -Feature Extractormentioning
confidence: 99%
“…The robustness against post-processing is not evaluated and it proposes in the future to detect image forgeries. The work in [4] examines the influence of several important CNN design choices for forensic applications, such as the use of a constrained convolutional layer or fixed high-pass filter at the beginning of the CNN. In [7,8], two techniques are combined for image tampering detection and localisation, leveraging characteristic footprints left on images by different camera models.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…Patches extraction: As state-of-the-art methods [4,8] for camera model classification gives promising results with small image patches, we also divide our image in small patches (64×64 pixels) as the second step of our robust framework for camera model identification. Indeed, the use of small image patches instead of full-resolution images better characterizes camera models in a reduced-size space.…”
Section: Camera Model Identificationmentioning
confidence: 99%
“…Recent efforts in detecting manipulations exploit deep learning based model in [6,4,36]. These include detection of generic manipulations [6,4], resampling [5], splicing [36] and bootleg [10]. The authors tested existing CNN network for steganalysis [35].…”
Section: Related Workmentioning
confidence: 99%